A “Congenitally Adapted” TFCC Tear in Radial Longitudinal Deficiency: Case Report and Review of Literature - Oestreich, Kerstin; Lindau, T.R. (Journal of Wrist Surgery, 2021)
We present a case of chronic wrist pain in a 14-year-old child with mild radial longitudinal deficiency and radiographic carpal collapse due to the absence of the scaphoid. Wrist arthroscopy demonstrated synovitis and a tear to the TFCC, which would be called “degenerative,” according to the Palmer classification. This was debrided, and the patient is still asymptomatic at long-term follow-up. Review of the literature found one paper with a similar observation in a 17-year-old adolescent. We propose that paediatric “degenerative” tears ought to be called “congenitally adapted” tears.
Keywords: Radial hemimelia; radial longitudinal deficiency; paediatric wrist pain; TFCC tear; TFCC classification